2015
DOI: 10.1080/23294515.2015.1117536
|View full text |Cite
|
Sign up to set email alerts
|

Patients' views concerning research on medical practices: Implications for consent

Abstract: Background Comparative effectiveness research (CER) and pragmatic clinical trials commonly test interventions that are in routine use and pose minimal incremental risk or burdens to patients who participate in this research. The objective of this study was to elicit the range of patients’ views and opinions regarding a variety of different types of research on usual medical practices, especially notification and authorization for them. Methods We conducted twelve focus groups with adults in five U.S. cities—… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
26
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 17 publications
4
26
0
Order By: Relevance
“…Similar types of misunderstandings have been documented in prior work 6 and highlight the challenges in helping people to understand research that so closely resembles regular medical care. It was also noteworthy and somewhat paradoxical that better understanding was not demonstrated consistently by participants who were randomly assigned to a scenario that included a written informed consent process.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Similar types of misunderstandings have been documented in prior work 6 and highlight the challenges in helping people to understand research that so closely resembles regular medical care. It was also noteworthy and somewhat paradoxical that better understanding was not demonstrated consistently by participants who were randomly assigned to a scenario that included a written informed consent process.…”
Section: Discussionsupporting
confidence: 59%
“…The study scenarios were drafted based on prior focus group findings 6 and input from the principal investigators involved with the NIH Health Care Systems Research Collaboratory, a national effort to conduct a series of major pragmatic clinical trials (https://www.nihcollaboratory.org/Pages/default.aspx), who reviewed the scenarios for clinical relevance and authenticity. The study team created posters, information sheets, and consent forms corresponding to notification and authorization approaches to accompany the hypothetical research scenarios, using samples of actual study documents as models.…”
Section: Methodsmentioning
confidence: 99%
“…By contrast, our earlier DES study of disclosure/consent preferences among patients found no difference in support for streamlined approaches for randomized studies as compared with observational designs . These findings are consistent with those of Kraft et al, who found that, while patients generally had similar consent preferences for both observational and randomized studies, IRB professionals distinguished between different study designs when expressing preferences regarding approaches for disclosure/consent . One explanation for this difference, suggested by prior qualitative work, is that IRB professionals may view observational research as less risky than randomized trials .…”
Section: Discussionsupporting
confidence: 83%
“…Prior qualitative studies have identified widespread misunderstanding about research on medical practices, particularly when participants compare it to the well-known archetype of a placebo-controlled clinical trial of new treatments. 1617 Our study suggests that at least some aspects of research on medical practices are difficult for people to understand without explicit and direct teaching. This is an important point for researchers who are interested in developing informed consent materials about topics that are unfamiliar to prospective participants, and it highlights the need for a clear approach to teaching key learning goals.…”
Section: Discussionmentioning
confidence: 90%